"For the good of their souls" : performing Christianity in eighteenth-century Mohawk country - Hart, William B. (Native Americans of the Northeast., 2020)
"In 1712, the Society for the Propagation of the Gospel in Foreign Parts opened their mission near present-day Albany, New York, and began baptizing residents of the nearby Mohawk village Tiononderoge, the easternmost nation of the Haudenosaunee (Iroquois) Confederacy. Within three years, about one-fifth of the Mohawks in the area began attending services. They even adapted versions of the service for use in private spaces, which potentially opened a door to an imagined faith community with the Protestants. Using the lens of performance theory to explain the ways in which the Mohawks considered converting and participating in Christian rituals, historian William B. Hart contends that Mohawks who prayed, sang hymns, submitted to baptism, took communion, and acquired literacy did so to protect their nation's sovereignty, fulfill their responsibility of reciprocity, serve their communities, and reinvent themselves. Performing Christianity was a means of "survivance," a strategy for sustaining Mohawk life and culture on their terms in a changing world"--